Formação docente para o ensino religioso: o caso dos professores de ensino religioso formados no curso de Ciências da Religião no Centro Universitário Municipal de São José/SC (USJ) - Silva, Franc Casagrande da (2020)
Religious Education in the Brazilian public school today, is a constitutive part of the laic State model, since this discipline initially of a confession character had a period of non-confession, but currently following the decisions of the Brazilian Supreme Court, it returns to the status of confession in public schools. However, it is observed that in the name of the citizen's right to receive the education he desires for his children from the public power, they show two historical perspectives on the matter in State and Municipal schools, because at Universities there is no Religious Education course at the university level, what we have in some university centers, colleges or universities, public or private, are courses in Theology and Science of Religion. This study aims to analyze the relationship between academic material and discipline of everyday school, on the didactic axis for Religious Education, aiming at teacher training and the closing of the Bachelor in Religious Sciences course at Centro Universitário Municipal São José/SC. It is a bibliographic research in which different means of reading on the theme were analyzed, maintaining the line of analysis of the Science of Religion, between the periods of 2009 to 2019, with a deepening in the works of former students of USJ. It was concluded that, the research found in the treatment of the collected data, that the ex-students of the course are working in the state school network of Santa Catarina, attending the largest school in the network in greater Florianópolis, taking with them the critical thinking formed in academy, applying the method of Science of Religion in the discipline of everyday school. Former students of Bachelor of Science in Religion are inserted in FONAPER and ASPERSC, as effective members in their functions in the promotion of RE by the State, in Forums and similar events